Municipal waste management scenario in Bangladesh: 3Rs perspective - Shumshunnahar, Mst. (International Journal Labs, 2025)
This study aims to analyze the current state of solid waste management in municipalities in Bangladesh, while also identifying the challenges they face and the opportunities that arise from their situations. This research employs a quantitative research approach, prioritizing primary data while integrating qualitative methods. Data collection involved objective-based questionnaires, content analysis of relevant documents, key information interviews, and a semi-structured survey method. The data have been organized, categorized, coded, computed, analyzed, summarized, presented, and tabulated (Statistical Packages for the Social Sciences). The primary objective is to evaluate the quantity and composition of Municipal Solid Waste in the study areas, and compare it to other municipalities in relation to the principles of the 3Rs (Reduce, Reuse, Recycle). The main objective of this study is to identify the challenges and opportunities related to waste generation, composition, and management practices. Furthermore, the study seeks to determine the limitations of the existing systems and explore potential improvements based on the three-resources framework. The study could explore the integration of technology in monitoring and managing waste services, assessing how these innovations can enhance transparency and accountability within local governments. This study could also explore the feasibility of establishing Ward Development Committees and their role in mobilizing community participation, along with assessing the financial implications of introducing extra charges for excessive waste production.